Effect of The Addition of Unripe Berlin Banana Flour on The Organoleptic Characteristics of Synbiotic Yogurt - Agustin, Firda; Damayati, Ratih Putri; Febriyatna, Ayu (P3M Politeknik Negeri Jember, 2024)
Synbiotic yogurt is a fermented milk product that combines probiotic bacteria with ingredients containing prebiotic components. Unripe banana flour (UBF) contains resistant starch (RS), which contributes to the development of prebiotics in synbiotic yogurt products. The research aimed to know the effect of the addition of UBF on the organoleptic characteristics of synbiotic yogurt. The research was carried out with an unripe Berlin banana. Four treatment groups included 2% inulin (P0), 1% UBF (P1), 2% UBF (P2), and 3% UBF (P3). The organoleptic characteristics include hedonic and hedonic quality tests using 48 semi-trained panelists. The data was statistically analyzed using the Kruskall-Wallis test followed by the Mann-Whitney test. The results of the hedonic test indicate that texture, aroma, and color significantly differed between groups (P<0.05), while taste did not significantly differ between groups (P>0.05). The hedonic quality test indicated that there were significant differences between groups in terms of texture, aroma, and color (P<0.05). However, there was no significant difference in taste between the groups (P>0.05). In conclusion, formula 2% UBF (P1) is the most preferable formula based on the organoleptic test.